RETRACTED: Peg-Asparaginase-Associated Pancreatitis in Chemotherapy-Treated Pediatric Patients: A 5-Year Retrospective Study - Zhang, Yun-yu; Yang, Qiu-shi; Qing, Xia; Li, Bi-ru; Qian, Juan; Wang, Ying; Ning, Bo-tao (Frontiers in Oncology, 2020)
Background Asparaginase-associated pancreatitis (AAP) is one of the most common complications occurring in patients with asparaginase-treated acute lymphoblastic leukemia (ALL). Peg-asparaginase (peg-asp), a chemically recombined asparaginase with lower hyposensitivity and better patient tolerance, is now approved as the first line asparaginase formulation in ALL chemotherapy regimens. Due to the differences in pharmacokinetic characteristics and administration procedure between l-asp and peg-asp, this study aimed to investigate the clinical manifestations of peg-asp-associated pancreatitis. Method Patients with peg-asp-associated pancreatitis diagnosed within a 5-year period (July 2014 to July 2019) were identified and retrospectively studied. The clinical manifestations, laboratory findings, and imaging results of patients with AAP were analyzed. AAP patients were further classified into mild/moderate and severe groups based on criteria used in previous studies. Clinical outcomes were compared between groups. Results A total of 38 patients were enrolled in this study. The underlying disease included ALL (n=35) and lymphoma (n=3). The majority of patients developed AAP during the first phase, called remission induction (n=26, 68.4%), after a median of 2 peg-asp doses (range: 1–11). The DVLP regimen (n=23) is the most common peg-asp regimen used in AAP patients. Abdominal pain occurred after a median of 14.5 days (range: 1–50) from the last peg-asp administration, accompanied by abdominal distension (n=14), nausea (n=17), vomiting (n=21), and fever (n=19). Serum amylase elevation was reported in all AAP patients, of whom 65.8% (n=25) exhibited an elevation in the level of this enzyme three times the upper normal level, fulfilling the Atlanta criteria. The level of serum lipase (median days of elevation=23 days, range: 4–75) was significantly elevated compared with that of serum amylase (median days of elevation=9 days, range: 2–71) and persisted at a markedly high level after the level of serum amylase returned to normal. Common local complications included abdominal ascites (n=10) and peripancreatic fluid collection (n=8). Approximately 42.1% (n=16) of patients with severe AAP experienced systemic complications (septic shock or hypovolemic shock) or severe local complications (pseudocyst), among whom 5 failed to recover. Approximately 84.8% (n=28/33) of the remaining patients resumed chemotherapy; among them, peg-asp formulation in 30.3% (n=10/33) of these patients was adjusted, while asparaginase treatment in 39.4% (n=13/33) was permanently discontinued. Five patients experienced an AAP relapse in later stages of asparaginase treatment. Comparison between mild/moderate and severe AAP patients showed a statistically significant difference in the number of pediatric intensive care unit stays (p=0.047), survival rate (p=0.009), AAP prognosis (p=0.047), and impacts on chemotherapy (p=0.024), revealing a better clinical outcome in mild/moderate AAP patients. Conclusion Early recognition and management of AAP is essential in reversing the severity of AAP. The existing AAP criteria had a low strength in determining the severity of pediatric AAP. A well-defined AAP definition could help distinguish patients with high anticipated risk for redeveloping AAP and ALL relapse, in order to prevent unnecessary withdrawal of asparaginase. Our study could serve as a basis for conducting future large cohort studies and for establishing an accurate definition of pediatric AAP.